Seasonal glacier change revealed from the real-time monitoring platform on Baishui River Glacier No.1 in Yulong Snow Mountain, Southeastern Qinghai–Tibet plateau - Chuya Wang; Yuande Yang; Shijin Wang; Songtao Ai; Yanjun Che; Junhao Wang; Leiyu Li; Fei Li (Annals of Glaciology)
The mass balance of glaciers requires more detailed and continuous observations to understand their seasonal change in relation to climate. Here, we designed and installed an automated real-time monitoring platform at 4645 m a.s.l. on the Baishui River Glacier No.1 to collect continuous high-resolution observational data, and analyzed the seasonal dynamic from glacier movement and surface mass balance from glacier melting and snow accumulation. The results showed that the platform moved northeastward ~12.9 m at a rate of 0.06 ± 0.02 m d−1 between September 2021 and April 2022. The surface mass balance showed a varied temporal period. July and August were the main ablation periods, while ablation decreased and ceased in September. The glacier neither melted nor accumulated much between October and December, but began to have rapid snow accumulation in January. The glacier surface temperature varied with the air temperature and showed significant inter-seasonal differences among monsoon, post-monsoon and winter seasons. The surface mass balance also exhibited a strong response to the air temperature changes, with an average decrease of 1°C the point mass balance increased by 0.11 m w.e. from monsoon to post-monsoon and 0.22 m w.e. from post-monsoon to winter. Moreover, we found snowfall caused a decrease in the glacier surface temperature by increasing the surface albedo.